Legal Certainty in Fintech Regulation: A Normative Study of Peer-to-Peer Lending Governance in Indonesia - Deo Renaldi Saputra; Melva Noya (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This article examines legal certainty within Indonesia’s peer-to-peer (P2P) lending regulatory framework through a doctrinal normative approach employing statutory, conceptual, and comparative analysis. The study evaluates the coherence of legislation governing financial supervision, electronic transactions, consumer protection, Sharia finance, data protection, and sustainable finance policy, alongside relevant OJK regulations and judicial decisions. The findings indicate that although Indonesia has established a comprehensive regulatory architecture, legal certainty remains challenged by normative fragmentation, dual governance structures between conventional and Sharia models, overlapping enforcement mandates, and procedural inconsistencies in dispute resolution. The regulatory sandbox mechanism and sustainability integration further complicate predictability where evaluative benchmarks and sanction gradations lack precise articulation. Comparative reflection on Islamic fintech governance and enforcement coordination highlights the importance of institutional synergy and codified supervisory alignment. The research concludes that strengthening cross-referencing norms, clarifying organizer liability standards, harmonizing jurisdictional competencies, and embedding enforceable sustainability and data protection obligations are necessary to enhance doctrinal coherence. Legal certainty emerges not merely from regulatory proliferation but from systematic hierarchical integration capable of reconciling innovation with constitutional rule-of-law principles in the digital financial sector